2013
DOI: 10.1038/emboj.2012.345
|View full text |Cite
|
Sign up to set email alerts
|

Role of Saw1 in Rad1/Rad10 complex assembly at recombination intermediates in budding yeast

Abstract: The Saccharomyces cerevisiae Rad1/Rad10 complex is a multifunctional, structure-specific endonuclease that processes UV-induced DNA lesions, recombination intermediates, and inter-strand DNA crosslinks. However, we do not know how Rad1/Rad10 recognizes these structurally distinct target molecules or how it is incorporated into the protein complexes capable of incising divergent substrates. Here, we have determined the order and hierarchy of assembly of the Rad1/Rad10 complex, Saw1, Slx4, and Msh2/Msh3 complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(111 citation statements)
references
References 47 publications
8
102
1
Order By: Relevance
“…We examined whether SSA and BIR could contribute to the Rad52-dependent suppression of dna2-K1080E and found that the deletion of Rad10, Saw1, and Tid1, important factors for SSA or BIR (76,98,99), did not affect the suppression (data not shown). It has also been shown that a subset of SCR events, which is facilitated by the RSC complex, could occur independently of Rad51 (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…We examined whether SSA and BIR could contribute to the Rad52-dependent suppression of dna2-K1080E and found that the deletion of Rad10, Saw1, and Tid1, important factors for SSA or BIR (76,98,99), did not affect the suppression (data not shown). It has also been shown that a subset of SCR events, which is facilitated by the RSC complex, could occur independently of Rad51 (78,79).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the 3′ NHTs must be removed to allow synthesis and subsequent ligation. Rad1-Rad10 is responsible for cleaving the tails, but requires partner proteins Msh2-Msh3 and Saw1 to be recruited to the 3′ NHTs [17, 19, 20]. Msh2-Msh3 has been proposed to stabilize the recombination intermediate to promote cleavage by Rad1-Rad10 [17, 20].…”
Section: Introductionmentioning
confidence: 99%
“…ChIP analysis revealed that SAW1 is required to recruit Rad1 to sites of SSA repair, indicating SAW1 function precedes flap trimming by the Rad1-Rad10 endonuclease in SSA [11]. A recent report showed that Saw1 has intrinsic affinity for flap and splayed arm DNAs and that binding of Saw1 to Rad1-Rad10 increases the affinity of Rad1-Rad10 binding to flap DNAs, especially those containing longer 3′ flaps [12]. A purified complex containing Saw1, Rad1 and Rad10 cleaves specific flap DNA structures in vitro [12].…”
Section: Introductionmentioning
confidence: 99%